Liposarcoma of the Thyroid Gland: A Case Report - Christian Manginstar; Marselus Merung; Denny Saleh; Leise Limpeleh; Enika Tilaar; Ridel Torar (Universitas Sam Ratulangi, 2024)
Abstract: Liposarcoma is one of the most common soft tissue tumors in adults. Liposarcoma is usually found in retroperitoneal organs and extremities, but rarely in the thyroid gland. We presented a case of dedifferentiated liposarcoma in the thyroid gland. A 56-year-old woman with a history of a lump in her neck for ten years. Malignancy was suspected due to the local extension of the tumor, therefore, complete resection of the tumor was performed. Histopathological examination showed a dedifferentiated liposarcoma. Two months post-surgery, the patient suffered from lung and brain metastases and was treated with lenvatinib. The complaints reduced and there was no significant side effect during therapy. The treatments for liposarcoma are surgery, radiotherapy, chemotherapy, and targeted therapy. Surgery followed by radiotherapy and chemotherapy is the option in the treatment of liposarcoma. This patient underwent surgery with the histopathological result of dedifferentiated thyroid liposarcoma. In the nine-month follow-up of therapy, there were no complaint of the patient. In this case, dedifferentiated liposarcoma in the thyroid gland with metastases was treated surgically followed by lenvatinib administration gave satisfactory result. Keyword: liposarcoma; thyroid gland; dedifferentiated liposarcoma; malignant tumor